Comparative Study On The Productivity And Profitability Of Commercial Broiler, Cockerel Of A Layer Strain And Cross-Bred (Rir × Fayoumi) Chicks - Sarkar, PK; Chowdhury, SD; Kabir, MH; Sarker, PK (Bangladesh Journal of Animal Science, 2012)
An experiment was conducted to compare the productivity and profitability of commercial broiler, cockerel and cross-bred (F1 RIR ? × Fayoumi ?) chicks up to target body weights of 850, 1000 and 1250g. Two hundred sixteen birds of 3 genotypes each of 72 birds having 18 chicks in each replication were considered. Commercial broiler starter diet was fed to experimental birds ad libitum. Similar care and management were provided to birds of all treatment groups. Commercial broilers attained the target weights of 850, 1000 and 1250g at the age of 21, 24 and 28 days respectively whereas cockerels attained weights close to those targets at 56, 63 and 74 days respectively and in the case of cross-breds, the days were 63, 77 and 90 for those target weights respectively. Feed conversion ratio (FCR) was best in broilers, followed by cockerels and cross-bred chicks respectively. The highest mortality (8.3%) was found in cross-bred group when reared up to target weight of 1250g. The mortality of broiler was 1.4% and no bird was died in cockerel group. Broiler was most profitable (21.11 Tk/kg live bird) at the target weight of 1250g whereas profit from cockerel varied little (21.78, 21.07 and 21.63 Tk/kg live bird against the target weights of 850, 1000 and 1250g respectively) amoung target weights. Therefore, appropriate weight to market these birds was at 850g to minimize the risk of diseases and other management works. Marketing of cross-bred chicks was most profitable (8.43 Tk/kg live bird) at 850g target weight and loss was incurred when rearing was continued up to 1250g. On the basis of results of productivity, it was concluded that commercial broiler, cockerel and cross-bred chicks could be reared upto 28, 56 and 63 days respectively to reach target weights close to 1250, 850 and 850g respectively to obtain maximum profit.? DOI: http://dx.doi.org/10.3329/bjas.v37i2.9886 BJAS 2008; 37(2): 89-98